Trend changes and factor analysis of endometrial hyperplasia in patients with polycystic ovarian syndrome based on the Korean National Health Insurance Database - Bora Park; Hakmo Lee; Suyeon Park; Eun Sil Lee; Jeong Jae Lee; Young Lee; Je Hyun Seo (BMC, 2022)
Abstract Background Polycystic ovary syndrome (PCOS) is a common endocrine disorder associated with an increased risk of other gynecological disorders, such as endometrial hyperplasia (EH). However, substantial factors in the comorbidity of EH and PCOS remain to be investigated. We analyzed trend changes in PCOS and factors related to the comorbidity of PCOS and EH using data from the Korea National Health Insurance (KNHI) claims database. Methods The data for this population-based study of people diagnosed with PCOS or EH in Korea from 2009 to 2016 were collected from the KNHI claims database between 2007 and 2017. We conducted a trend analysis of the prevalence and incidence of PCOS and EH. In addition, we performed a logistic regression analysis to identify risk factors associated with EH incidence in people with PCOS using the matched case-control methodology. Results The average annual growth rate of the incidence of PCOS was 14.1% from 2009 to 2016, whereas the EH rate increased by only 3.4% annually. Comorbidities, type 2 diabetes, obesity, hypertension, hyperlipidemia, and infertility, increased the risk of EH in PCOS patients. Additionally, the cumulative duration of oral contraceptive & progestin treatment for PCOS correlated highly with the comorbidity of EH and PCOS. Conclusions We confirmed the relationship between PCOS and EH using big data suitable for time series analyses of the diagnosis and treatment of diseases. Endometrial evaluation should be done with more caution if oral contraceptives & progestins have been used for a long time.